Validity Self-Regulated Learning Assessment on Student’s Mathematics Learning: Realibility Study - Alifa Shafira Dina (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
Self-Regulated Learning is a student's skill in regulating themselves during the learning process, including learning initiatives, goal setting, monitoring progress, and evaluating learning outcomes. The chosen learning strategy must be able to measure the extent of their mastery of the learning material and be able to make students aware of the importance of using learning strategies. This study aims to test the validity and reliability of the student self-regulated learning measurement assessment using SPSS software. The assessment was tested on 34 high school students. Based on the results of the validity test using the Pearson Product Moment technique, from 29 statements, all statements were declared valid. The decision taken was that no statements were made, because all statements were valid and represented all indicators of the self-regulated learning questionnaire. In addition, the Cronbach's Alpha value was obtained at 0.892. Therefore, the self-regulated learning questionnaire submitted was said to be reliable